Prostate Specific Antigen (PSA): Normal Reference Value in Bangladeshi Male, a Retrospective PSA Analysis of 765 Male (Anwer Khan Modern Medical College Journal, 2014)
Prostate specific antigen (PSA) is an important tool for the diagnosis, prognosis and follow up of prostatic cancer, the most common malignancy of the male throughout the world. It is safe, reliable, specific, noninvasive test if done properly. However there are many benign, inflammatory and other prostatic conditions which can also give rise to elevated PSA value and thus limits its use. Different methods of estimation may also give rise to variable PSA level. More over the normal reference range may be variable depending on the age, geographic situation, environmental conditions and other factors. The normal reference range mentioned in the texts is based on findings in the developed countries. No effort was made before to see the normal reference PSA value among Bangladeshi male population. With this background the present study was undertaken to determine the normal reference value of PSA in Bangladeshi population. It is evident form the present study that the normal reference PSA value for Bangladeshi male in different age groups are lower in comparison to that of upper limit of normal reference value mentioned in the text. DOI: http://dx.doi.org/10.3329/akmmcj.v5i1.18766 Anwer Khan Modern Medical College Journal Vol. 5, No. 1: January 2014, Pages 19-22